2021
DOI: 10.1016/j.sjbs.2021.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Murine Double Minute 2 Gene (MDM2) rs937283A/G variant significantly increases the susceptibility to breast cancer in Saudi Women

Abstract: Breast cancer is predominant causes of mortality in women worldwide. Genetic polymorphisms have a significant role in breast cancer aetiology. TP53 and its inhibitor the murine double minute 2 (MDM2 ) genes encode proteins that have crucial functions in the DNA damage response. The allelic variations within these genes could influence the susceptibility to breast cancer. MDM2 promotor polymorphism rs937283A/G has a role in susceptibility to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…So far, some genes, including MDM2, CD82, MED1, miR-34a, miR-520h, HDAC1, CYP1A1, NTN4, EIF4EBP1, ATG4A, BAG1, MAP1LC3A, SERPINA1, MMP1, and MMP9 are identified as the risk factors of breast cancer. Relevant studies on these genes concluded that they could develop breast cancer (10)(11)(12)(13)(14)(15)(16)(17). Similarly, some genes, including PTEN, P62, NOD2, TP53, MSH3, POFUT1, RPRD1B, EIF6, MGP, FGF2, OGDHL, CYP24A1, WNT1, KLF5, WNT16, CLDN1, and TET3 have been effective in CRC development (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…So far, some genes, including MDM2, CD82, MED1, miR-34a, miR-520h, HDAC1, CYP1A1, NTN4, EIF4EBP1, ATG4A, BAG1, MAP1LC3A, SERPINA1, MMP1, and MMP9 are identified as the risk factors of breast cancer. Relevant studies on these genes concluded that they could develop breast cancer (10)(11)(12)(13)(14)(15)(16)(17). Similarly, some genes, including PTEN, P62, NOD2, TP53, MSH3, POFUT1, RPRD1B, EIF6, MGP, FGF2, OGDHL, CYP24A1, WNT1, KLF5, WNT16, CLDN1, and TET3 have been effective in CRC development (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%